The Effectiveness of Sungkai Leaf (Peronema canescens Jack.) Extract Gel on the Collagen Density of Incision Wounds in Vivo - Clarissa Ester Diana Putri; Herlina Eka Shinta; Fatmaria Fatmaria; Elsa Trinovita (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
An incision is an open wound resulting in skin injury and underlying tissues. The wound-healing process involves a proliferative phase that produces collagen. Sungkai leaves (Peronema canescens Jack.) can be used as an alternative therapy for wound healing because it contains flavonoids, tannins, and saponins that stimulate fibroblasts to synthesize collagen. This study aimed to determine the effectiveness of sungkai leaf extract gel in healing incision wounds in vivo based on collagen density scoring. Twenty-five Wistar rats (Rattus norvegicus) were randomly divided into five groups, the negative control group (K1) was given a gelling agent CMC 1%, the positive control group (K2) was given bioplacenton gel 1%, the treatment group (K3, K4, K5) was given a gel sungkai leaf extract concentration of 5, 10, and 15. The treatment is given topically at the incision site of the incision site of 0.1 g once a day for 14 days. The rats were euthanized on the fifteenth day, and the incision area was excised for histopathological preparation. The data obtained were analyzed using Kruskal-Wallis with SPSS 26. The test results showed p=0.010, meaning there is a significant difference (p<0.05) between the entire treatment. Based on these results, the K4 group (Sungkai leaf extract gel concentration of 10%) showed the highest collagen density scoring results compared to other treatments. This study concludes that sungkai leaves effectively heal incision wounds in Wistar rats based on collagen density scoring parameter.